2009
DOI: 10.4067/s0718-40262009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Resultados perioperatorios y sobrevida alejada de la pancreatoduodenectomía con resección vascular

Abstract: Pancreaticoduodenectomy with vascular resection. Perioperative results and longterm survivalBackground: Pancreaticoduodenectomy (PDD) with vascular resection (VR) of the portal and superior mesenteric vein for locally advanced periampullary tumors is controversial. Aim: To evaluate the perioperative results and long-term survival of PDD with VR. Patients and Methods: Retrospective study. We included patients with periampullary tumors who underwent a PDD with VR between 1990 and 2008. We compared perioperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Lymph node positivity has been reported as a marker of poor prognosis in patients undergoing pancreatoduodenectomy. 20,21,25,26 The effect of number of lymph nodes retrieved on long-term survival has also been studied with some support in literature. 22,28 However, our study including the one by Farid et al 10 Previous studies have tried to validate LNR as a categorical variable by either using cut-off levels 10,25 or by grouping them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymph node positivity has been reported as a marker of poor prognosis in patients undergoing pancreatoduodenectomy. 20,21,25,26 The effect of number of lymph nodes retrieved on long-term survival has also been studied with some support in literature. 22,28 However, our study including the one by Farid et al 10 Previous studies have tried to validate LNR as a categorical variable by either using cut-off levels 10,25 or by grouping them.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,25,26 The effect of number of lymph nodes retrieved on long-term survival has also been studied with some support in literature. 22,28 However, our study including the one by Farid et al 10 Previous studies have tried to validate LNR as a categorical variable by either using cut-off levels 10,25 or by grouping them. 4,9,20,22 Farid et al 10 & Shamseddine et al 28 found the LNR >0.2 to be an important factor in determining prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…ganglios de la arteria hepática, del ligamento hepatoduodenal y los ganglios en relación a la arteria mesentérica superior. En casos de invasión local de la vena porta o mesentérica superior se realiza una resección de esta en casos seleccionados 8 . Se toma muestra para biopsia contemporánea de los márgenes de la vía biliar y de la sección del páncreas.…”
unclassified